Blockchain-Based Electronic Health Record: Systematic Literature Review - Nehal Ettaloui; Sara Arezki; Taoufiq Gadi (Human Behavior and Emerging Technologies)
Electronic health records (EHRs) represent an innovative approach to constructing a distributed data analysis framework for managing health data within its original location. The integration of blockchain technology into EHR systems offers substantial improvements in security, privacy, and transparency, thus enhancing overall management efficiency. Our research spanned from January 2017 to December 2022, conducting a meticulous systematic literature review across reputable databases such as Scopus, IEEE Xplore, Springer, PubMed Central, and ScienceDirect. This comprehensive search, finalized in December 2022, utilized stringent inclusion and exclusion criteria to ensure the selection of high-quality articles, thereby guaranteeing transparency and unbiased results. Through this systematic review, our primary objective was to explore, assess, and analyze the diverse architectures, proposed models, limitations, and future trajectories of blockchain-enabled EHR systems. Our emphasis was on highlighting blockchain’s adaptability and robustness in healthcare contexts while identifying potential challenges and areas for further investigation. Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, we scrutinized more than 600 scientific studies, culminating in the selection of 31 articles that met our rigorous inclusion standards. Our technical and architectural evaluations delved into critical aspects such as privacy, security, authentication, availability, data control, storage, and resource consumption. Our research outcomes underscore the effective resolution of security, privacy, and availability concerns in EHRs through blockchain integration. However, we observed potential trade-offs, including impacts on performance, resource utilization, and regulatory compliance. To address these complexities, we introduce an integrated framework designed to mitigate key challenges and deliver substantial value within this domain.